Sandry's book - Pierce, Tamora (Pierce, Tamora. Circle of magic (Full Cast Audio (Firm)), 2002)
This is a story about craft, about work, about magic, and most of all about the pleasure and difficulty of friendship. It begins when four young misfits with a talent for magic (and trouble!) arrive at Winding Circle Temple. Despite their differences, Sandry (the noble), Tris (the merchant girl), Daja (the trader), and Briar (the "streetrat") find themselves bound together ina Circle of Magic--a circle they will need when they face crushing danger in a white-knuckle climax that will have listeners glued to the edges of their seats.